Estimating hydraulic conductivities through the measurement of streaming potentials - Mazibuko, Jemias Clifford (University of the Free State, 2019)
The hydraulic parameters of heterogeneous aquifers are often estimated by conducting pumping (and recovery) tests during which the drawdown in a borehole intersecting the aquifer is measured over time, and by interpreting the data after making a number of assumptions about the aquifer conditions. The interpreted values of the hydraulic parameters are then considered to be average values that represent the properties of the bulk aquifer without taking into account local heterogeneities and anisotropies. An alternative and more economic approach is to measure streaming potentials in the vicinity of the borehole being tested. The streaming potential method is a non-invasive geophysical method that measures electrical signals generated by groundwater flow in the subsurface through a process known as electrokinetic coupling. This method allows data to be recorded at a high spatial density around the borehole. The interpretation of streaming potential data in terms of aquifer hydraulic parameters is facilitated by a coupled flow relationship which links the streaming potential gradient to the hydraulic gradient through a constant of proportionality called the electrokinetic coupling coefficient. In the current study, field measurements of streaming potentials were taken during the pumping and recovery phases of pumping tests conducted at two sites with dissimilar geological and geohydrological conditions. The recorded streaming potential data were interpreted by calculating the hydraulic head gradient from the streaming potential gradient, and by using the potential field analytical solution for the transient mode, which relates the streaming potential field directly to the average hydraulic conductivity. Hydraulic conductivity values estimated from the streaming potential method were of the same order as values determined from the analysis of drawdown data, with a relative error of 0.2. This study demonstrates that the streaming potential method is a viable tool to compliment pumping tests and provide a spatial representation of the hydraulic parameters.
Dissertation (M.Sc. (Institute for Groundwater Studies))--University of the Free State, 2019
Keywords: Streaming potential method; Electrokinetic coupling; Hydraulic parameters; Heterogeneous acquifers